2017
DOI: 10.1007/s10924-017-1071-9
|View full text |Cite
|
Sign up to set email alerts
|

All Natural High-Density Fiber- and Particleboards from Hemp Fibers or Rice Husk Particles

Abstract: In the present study, long hemp fibers and rice husk particles have been used for producing all natural-based boards for building, automotive and in-door furniture, employing a simple and economic transformation process (namely, compression molding). In order to have the required consistence and mechanical strength, cornstarch was employed as binder. By this way, fiber-and particleboards have been prepared and characterized in terms of morphology, mechanical properties (flexural modulus and strength). The infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…The recovery of this waste material would improve the sustainability of this agricultural activity and help to reduce the environmental impact of other means of disposing of it. So far rice husk has been recycled only for low-value applications, some studies have described the incorporation of rice husk in thermal insulation material [19,20], lightweight concrete [21], composite with cork and rubber [22], and starch [23]. The rice husk was also added in plastic composites with low density polyethylene (LDPE) [24], high density polyethylene (HDPE) [25] polylactic acid (PLA) [26] polypropylene (PP) [27] and polyvinyl chloride (PVC) [28].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of this waste material would improve the sustainability of this agricultural activity and help to reduce the environmental impact of other means of disposing of it. So far rice husk has been recycled only for low-value applications, some studies have described the incorporation of rice husk in thermal insulation material [19,20], lightweight concrete [21], composite with cork and rubber [22], and starch [23]. The rice husk was also added in plastic composites with low density polyethylene (LDPE) [24], high density polyethylene (HDPE) [25] polylactic acid (PLA) [26] polypropylene (PP) [27] and polyvinyl chloride (PVC) [28].…”
Section: Introductionmentioning
confidence: 99%
“…One of the established markets for composites with natural fillers is their molding into panels for automotive interior applications such as door panels/inserts, trunk liners, spare wheel covers, parcel trays, headliners, columns, and much more or partial replacement of wooden part in furniture . Several researchers have worked with fibers for developing thermoplastic and thermoset composites .…”
Section: Introductionmentioning
confidence: 99%
“…RH may be used as brick kilns, in the rice parboiling process, in a furnace, raw material for sodium silicate production, cleaning and polishing agent in metals, and various machine industries [75,76]. Use of RH has been proposed for building materials like panels and boards paving the way for replacement of wood which has been used traditionally [77,78]. Antunes et al Developed panels using Rice Husk and earth and improved properties were observed ranging from tensile, compressive strength to moisture absorption.…”
Section: Application Of Rh Based Compositesmentioning
confidence: 99%